Comparative Analysis of Composites Based on Corresponding Natural Minerals and their Strength - Jafarov, V.J.; Manafov, M.A.; Bektashi, N.R.; Alimirzaeva, N.A.; Khalilova, S.M.; Salahova, S.A.; Musaeva, G.H. (Herald of Azerbaijan Engineering Academy, 2025)
The article provides a comparative analysis of the degree of strength (tensile strength) of composites based on fillers of various compositions. In this direction, research was conducted and results were obtained taking into account a number of filler characteristics. The corresponding fillers were brought from different places and made suitable for laboratory testing. As a result of comparing the ultimate tensile strength values, it was determined which filler is more suitable and superior to others. The fillers are based on natural mineral rocks, clays, etc., brought from several regions of Azerbaijan. The value of the results directly depends on the dispersion of the filler, the relief structure of the area, the mineralogical wealth of the extracted sources and a number of factors.